Analysis of methods of using the Raspberry PI platform in the training of computer engineers - Bilash, D. A. (ХНУРЕ, 2021)
Raspberry Pi is the name of a series of single-board computers and high-performance microcontrollers. First of them was launched by the Raspberry Pi Foundation in 2012. A UK charity that aims to teach people in computing and provide them with easy knowledge in the Internet of Things, giving a big opportunity to use their products. Also it is cheap and costs less than 35 $ and there is a model that costs only 5$.
Keywords: Raspberry PI